An Enhanced Sine Cosine Algorithm for Feature Selection in Network Intrusion Detection - zahra asgari varzaneh; soodeh hosseini (Computer and Knowledge Engineering)
For computer networks to remain secure, intrusion detection is essential. Analyzing network traffic data is part of this activity to spot possible cyber threats. However, the curse of dimensionality presents a challenge because there are so many dimensions in the data. To overcome this challenge, feature selection is essential to creating a successful intrusion detection system. It involves removing irrelevant and redundant features, which enhances the classification model's accuracy and lowers the dimensionality of the feature space. Metaheuristic algorithms are optimization techniques inspired by nature and are well-suited to choose features for network intrusion detection. They are effective in exploring large search spaces and have been widely used for this purpose. In this study, we improve the Sine Cosine Algorithm named ISCA for feature selection by introducing a controlling parameter to balance exploration and exploitation. Based on the NSL-KDD dataset, the results show that compared to other competing algorithms, the ISCA performs better than other metaheuristic algorithms in terms of both the number of features selected and the accuracy of classification.